Does economic freedom affect green economic growth? Analyses of mediation, moderation, and heterogeneity in EU and non-EU countries - Hou, Xiaohuan; Jin, Jiafei; Feng, Yulei (Frontiers in Environmental Science, 2025)
IntroductionEconomic freedom is widely regarded as a key determinant of economic prosperity. However, its influence on green economic growth (GEG), particularly within the context of sustainable development, remains underexplored. This study seeks to address this gap by examining the relationship between economic freedom and GEG, with a focus on both European Union (EU) and non-EU countries.MethodsUsing panel data from 28 EU and non-EU countries between 2012 and 2021, the study employs a two-way fixed effects model to explore the impact of economic freedom on GEG. The analysis incorporates mediation, moderation, and heterogeneity testing to understand the various factors at play. Energy security risk is tested as a mediating factor, while government efficiency and corruption control are assessed for their moderating roles.ResultsThe findings reveal that economic freedom significantly promotes GEG, with energy security risk serving as a key mediator. Specifically, higher economic freedom reduces energy security risks, which subsequently supports the growth of a green economy. Moreover, government efficiency and corruption control are found to moderate the relationship, enhancing the positive impact of economic freedom on GEG, particularly in non-EU countries. Heterogeneity analysis shows that economic freedom has a significant positive effect on GEG in non-EU countries, but no such effect is observed in EU countries, likely due to stricter environmental regulations and more extensive social welfare systems.DiscussionThese results suggest that while economic freedom plays a positive role in fostering GEG, the effectiveness of this relationship is contingent upon the regulatory environment, including government efficiency and corruption control. Policymakers are encouraged to strengthen regulatory frameworks, improve governmental efficiency, and manage energy security risks to create an environment conducive to sustainable green economic growth.